2015
DOI: 10.7845/kjm.2015.5018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gut bacterial diversity and exploration of cellulose-degrading bacteria in xylophagous insects

Abstract: In this study, gut bacterial communities in xylophagous insects were analyzed using the pyrosequencing of 16S rRNA genes for their potential biotechnological applications in lignocelluloses degradation. The result showed that operational taxonomic units (OTUs), species richness and diversity index were higher in the hindgut than in the midgut of all insect samples analyzed. The dominant phyla or classes were Firmicutes (54.0%), Bacteroidetes (14.5%), γ-Proteobacteria (12.3%) in all xylophagous insects except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…It is believed that Lactococcus lactis , which was dormant on plant surfaces, proliferated in the intestines of insects after feeding [ 63 ]. Some other members of Lactococcus have been reported to be associated with fermentation and to assist longicorn beetles in the degradation of cellulose [ 12 , 64 , 65 ]. Acinetobacter was found to have lignin degradation activity in previous experiments [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that Lactococcus lactis , which was dormant on plant surfaces, proliferated in the intestines of insects after feeding [ 63 ]. Some other members of Lactococcus have been reported to be associated with fermentation and to assist longicorn beetles in the degradation of cellulose [ 12 , 64 , 65 ]. Acinetobacter was found to have lignin degradation activity in previous experiments [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…could be an ideal agent for expressing insecticidal protein in M. alternatus midguts, which would represent a new use of microbes to control M. alternatus. Furthermore, the cellulose-degrading bacterial genera Stenotrophomonas, Gryllotalpicola, and Pseudoxanthomonas [49,52] were positively correlated with Serratia. In contrast, the genera Gp1, Gp2, Gp3, Saccharibacteria, Escherichia/Shigella, Bradyrhizobium, Sphingomonas, Terriglobus, Burkholderia, and Mucilaginibacter were negatively correlated with Serratia, and they are associated with soil pH, plant growth, and cellulose degradation [39,42,44,45].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the genus Gryllotalpicola was isolated from the midguts of Megopis sinica, M. alternatus, and Reticulitermes speratus, while the genus Cellulomonas was isolated from both the midgut and hindgut of M. sinica and M. alternatus [52, 53] and from the stem of P. contorta and the needles of Thuja plicata [29]. In this study, however, Gryllotalpicola had a relative abundance of only 0.25% in the midgut of M. alternatus, and Cellulomonas was not found in the midgut of M. alternatus.Both Gryllotalpicola and Cellulomonas can degrade cellulose[52], which is the main nutrient component in the food of wood-boring insects and plays an important role in the growth and development of pests[54]. Therefore, Gryllotalpicola sp.…”
mentioning
confidence: 99%
“…Shi et al found that pinewood nematode infection changes the physical and chemical properties of the soil and the bacterial community composition and diversity; however, Acidobacteria was the predominant bacteria in nematodeinfected soil, which had a lower pH than the uninfected soil [35]. It has been reported that the genus Gryllotalpicola was isolated from the midguts of Megopis sinica, M. alternatus, and Reticulitermes speratus, while the genus Cellulomonas was isolated from both the midgut and hindgut of M. sinica and M. alternatus [52,53] and from the stem of P. contorta and the needles of Thuja plicata [29]. In this study, however, Gryllotalpicola had a relative abundance of only 0.25% in the midgut of M. alternatus, and Cellulomonas was not found in the midgut of M. alternatus.…”
Section: Discussionmentioning
confidence: 99%
“…Both Gryllotalpicola and Cellulomonas can degrade cellulose [52], which is the main nutrient component in the food of wood-boring insects and plays an important role in the growth and development of pests [54]. Therefore, Gryllotalpicola sp.…”
Section: Discussionmentioning
confidence: 99%